Komparasi Model Pembelajaran Kooperatif Tipe Examples Non Examples dan Picture and Picture terhadap Hasil Belajar Siswa - Feladi, Vindo; Lusia, Apolonia; Henita, Henita; Losta, Iga; Dulhadi, Dulhadi (Research in Education and Technology (REGY), 2023)
This study aims to determine the comparison of cooperative learning models of the Examples Non-Examples and Picture And Picture types on student learning outcomes on internet hardware material in terms of learning motivation in class X  SMA  Karya Sekadau,    Regency.  The  research  method  uses  the experimental method, a form of factorial designThe research instrument was a test  in  the  form  of  multiple choice questions and  a  questionnaire.  The  data obtained were analyzed using two-way anava. The results of the anava test show: 1) There are differences in learning outcomes after being treated with cooperative learning models of the Examples Non Examples and Picture and Picture types on internet hardware material in class X SMA Karya Sekadau Regency with  the  Examples Non  Examples models, 2)  There  are  differences learning outcomes of students who have high learning motivation with students who have low learning motivation on internet hardware material in class X SMA Karya Sekadau Regency, 3) There is interaction of learning models with learning motivation on student learning outcomes on internet hardware material in class X SMA Karya Sekadau Regency with Model Examples Non Examples.